Elusive equality : gender, citizenship, and the limits of democracy in Czechoslovakia, 1918-1950 - Feinberg, Melissa (Series in Russian and East European studies., 2006)
"Through extensive original research, Melissa Feinberg assembles a compelling account of how early Czech progress in women's rights, tied to democratic reforms, eventually lost momentum in the face of political challenges facing the state in a young republic. Elusive Equality offers a prism to help sharpen our view of the evolution of twentieth-century European democracy and provides a cautionary tale for all who want to see democratic governments thrive."--Jacket